Integrating technology into teaching and learning : concepts and applications : an Asia-Pacific perspective - Williams, Michael D. (Singapore : Pearson Education Asia Pte. Ltd., 2000)
The book is intended for teachers, school administrators, teacher-trainees, teacher-educators, and in fact, anyone who in interested in how IT (information technology) can be used to improve the processes of teaching and learning.
Part 1.General issues for teachers -- 1. Introduction: what is technology integration? -- 2. Instructional planning -- 3.Visual design: principles and applications -- Part 2. Integrating software into lessons -- 4. Using hypermedia: the teacher's perspective -- 5. Learning theories and IT: the computer as a tutor -- 6. Evaluating computer-based educational resources -- Part 3. Practical issues -- 7. Managing IT classrooms -- 8. The internet in education -- 9. Cooperative learning and IT -- Part 4. Higher-level thinking and creativity -- 10. Learning theories and IT: the computer as a tool -- 11. Thinking skills and creativity: student projects using IT -- 12. Supporting student-centered learning with IT -- Appendix - Learning ten computer programs in a month.
Keywords: EDUCATIONAL TECHNOLOGY